Tom Clancy command and control [compact disc, unabridged] - Cameron, Marc; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 2023)
President Jack Ryan travels to Colombia to support the president who is facing a challenge from autocratic forces. What seems like an ordinary opportunity to preach the values of democracy quickly turns into a nightmare when a full-blown military coup erupts. President Ryan and his Secret Service team are cut off and out of communication. In Washington, the Vice President is coordinating a military response, but there's still one more obstacle. The Russians recognize an opportunity when one presents itself. They've hired a private military contractor to do the unthinkable, use the cover of the coup to assassinate President Jack Ryan.